(untitled) (Praxis Educativa, 2026)
This article documents lessons learnt from the implementation of two co-territorial teacher support strategies designed to strengthen the practical training pathways for trainee teachers on the Bachelor’s degree programmes in pre-school, primary and distance secondary education at the Escuela Normal Superior de Tehuacán. This teacher-training institution is situated in an ethnically and linguistically diverse region (Nahuatl, Ngigua, Mixtec, Mazatec) affected by water stress, internal armed conflict, displacement and enforced disappearance, gender-based violence, energy transitions, a profound digital divide, structural inequality, and acute vulnerability. The research is currently in a consolidation phase, and we aim to explore, through comparative analysis, how our educational research findings might be extrapolated to other contexts, particularly within Abya Yala. In conclusion, we seek to offer reflections that strengthen the formative evaluation of teaching in order to redefine our historical role from the perspective of ethno-territorial advocacy and community promotion, and not merely from the educational technocracy that validates teaching experience solely on the basis of the techniques, tools or strategies implemented. That is why our perspective on the educational model known as the Nueva Escuela Mexicana is a situated, reflective and contextualised critique, informed by our experiences within educational communities as teachers within co-learning groups, and grounded in a spirit of active listening alongside future generations of teachers who have been trained under the 2022 programme in Tehuacán, Puebla, Mexico.